SAK EMKM IMPLEMENTATION IN MICRO AND SMALL ENTERPRISES: EVIDENCE FROM AN INDONESIAN GOLD RETAIL BUSINESS - mia agustina; Annisa Nurislami; Shafa Ardhita Putri; Anisa Defi Julia; Rimi Gusliana Mais (Jurnal Ilmiah Mahasiswa Akuntansi Universitas Tulungagung, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in Indonesia's economy; however, many continue to experience difficulties in preparing financial statements that comply with applicable accounting standards. Despite the availability of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), empirical evidence concerning its implementation in gold retail businesses remains limited, particularly considering the sector's distinctive characteristics of high-value inventories and rapid price fluctuations. This study aims to evaluate the implementation of SAK EMKM at Sinar Baru Gold Store, assess the conformity of its existing bookkeeping practices with the standard, and reconstruct financial statements in accordance with SAK EMKM. A qualitative descriptive case study approach was employed using primary data obtained through semi-structured interviews with the business owner, direct observation, and financial transaction records covering the period from September to October 2025. Data were analyzed descriptively by comparing the enterprise's existing accounting practices with the recognition, measurement, presentation, and disclosure requirements of SAK EMKM. The findings reveal that the enterprise has not fully implemented SAK EMKM because its bookkeeping remains limited to recording daily cash receipts and disbursements without preparing complete financial statements. Nevertheless, the reconstructed financial statements indicate that the business maintains stable financial performance, positive profitability, strong liquidity, and sufficient financial information to produce standardized reports. The study contributes theoretically by extending the literature on SAK EMKM implementation within the underexplored gold retail sector and provides practical guidance for MSME owners, accounting practitioners, and policymakers in promoting standardized financial reporting, improving accounting literacy, and strengthening the sustainability and credibility of MSMEs.